2015
DOI: 10.1021/acs.biomac.5b01474
|View full text |Cite
|
Sign up to set email alerts
|

Dual Stimuli-Responsive Vesicular Nanospheres Fabricated by Lipopolymer Hybrids for Tumor-Targeted Photodynamic Therapy

Abstract: Smart delivery system of photosensitizer chlorin e6 (Ce6) has been developed for targeted photodynamic therapy (PDT). Simple self-assemblies of the mixtures comprising soybean lecithin derived phosphatidylcholine (PC), phosphatidylethanolamine-poly(L-histidine)40 (PE-p(His)40), and folic acid (FA) conjugated phosphatidylethanolamine-poly(N-isopropylacrylamide)40 (PE-p(NIPAM)40-FA) in different ratios yield smart nanospheres characterized by (i) stable and uniform particle size (∼100 nm), (ii) positive surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…[34] Kim et al designed a pH and temperature dual-responsive lipopolymer hybrid system (Ce6@VNS) containing Ce6, phosphatidylcholine (PC), the pH-responsive phosphatidylethanolamine (PE)-p(His) conjugate, along with the temperature responsive FA conjugated PE-p(NIPAM). [81] Self-assembly upon mixing these components creates nanospheres, which have a Adv. Funct.…”
Section: Dualresponsive Apssmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Kim et al designed a pH and temperature dual-responsive lipopolymer hybrid system (Ce6@VNS) containing Ce6, phosphatidylcholine (PC), the pH-responsive phosphatidylethanolamine (PE)-p(His) conjugate, along with the temperature responsive FA conjugated PE-p(NIPAM). [81] Self-assembly upon mixing these components creates nanospheres, which have a Adv. Funct.…”
Section: Dualresponsive Apssmentioning
confidence: 99%
“…Compared to free Ce6, Ce6@VNS has a significantly enhanced photocytotoxicity against targeted KB cells. [81] In a more recent report, Torres et al also described a pH and thiol dual-responsive aPS that contains a pyrene-modified SiPc group, which should attract great interest as a multifunctional theranostic agent. [82] Recently, Liu et al described a series of special fluorophores that possess aggregation-induced emission (AIE) characteristics that can be used advantageously in the design of new aPSs.…”
Section: Figure 12mentioning
confidence: 99%
“…To enhance the therapeutic efficacy, dual or multi stimuli‐responsive nanocarriers, including pH/temperature (T), pH/redox, pH/magnetic field, T/redox, T/enzymatic, T/pH/redox, T/pH/magnetic field, and pH/redox/magnetic field, have been considered as intelligent nanocarriers . Recently, our research group reported the pH/T dual stimuli‐responsive delivery of Dox and chlorin e6 in anticancer therapy . The intracellular uniqueness of cancer cells has been exploited by combining pH/redox dual stimuli‐responsive nanocarriers as a suitable option for accelerating drug release in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the passive targeted efficiency of the EPR effect is insufficient to achieve a high enough concentration of drug in malignant tumor tissues. To conquer this limitation, targeting ligands that can distinguish cancer cells from normal ones and stimulate receptor‐mediated endocytosis, have been implemented in several drug delivery systems …”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Nevertheless, the passivetargeted efficiency of the EPR effect is insufficient to achieve ah igh enough concentration of drugi nm alignant tumor tissues.T o conquer this limitation, targeting ligandst hat can distinguish cancer cells from normal ones and stimulate receptor-mediated endocytosis, have been implemented in severald rug delivery systems. [14][15][16][17] The objective of this study was to build mixed micelles based on two functional co-polymers, including the redox-sensitive polymer-drug conjugate methoxy poly(ethylene glycol)poly(g-benzyl l-glutamate)-disulfide-docetaxel (PEG-PBLG-SS-DTX) and the actively targeting methoxy poly(ethylene glycol)folic acid (PEG-FA), for enhanced targets pecificity and improveda nticancere fficiency of docetaxel (DTX). The spherical PEG-PBLG-SS-DTX/PEG-FAm ixed micelles prepared by the dialysis methodr evealed an arrowly distributed size at 129.7 AE 2.1 nm with low polydispersity of 0.10 AE 0.02.…”
Section: Introductionmentioning
confidence: 99%